Shaping Student Discipline Characters Through the Role of Teachers at Muhammadiyah 2 Sidoarjo Elementary School - Abdullah Mujahidin; Ida Rindaningsih (Journal of Islamic and Muhammadiyah Studies, 2023)
Discipline is the attitude of obeying the rules in forming moral character. Therefore, discipline becomes an important issue. In this regard, the role of teachers in schools is very necessary to form a strong student character. The aims of this study are to: (1) play the role of the teacher in shaping the discipline of fifth grade students of SD Muhammadiyah 2 Sidoarjo, (2) support the supporting factors and the formation of disciplinary character of students in class V of SD Muhammadiyah 2 Sidoarjo. A qualitative approach is a type of qualitative descriptive research used to achieve the above objectives. The central tool is the researcher himself and the data collection techniques used are observation, interviews and documentation. Data analysis by organizing data, presenting data, and drawing conclusions. The results showed that (1) the teacher's role in shaping the discipline character of fifth grade students at SD Muhammadiyah 2 Sidoarjo included compliance with rules, punctuality, and responsibility in carrying out tasks; ricefield. (2) The factors that shape the character of this field include supporting school programs, building good partnerships in the school environment, and playing an active role in student development to support teachers and parents. In addition, barriers include lack of proper parental cooperation, limited teacher supervision of students, influential peers, and lack of technology use.